Exploring the impact of influencers’ characteristics on the cosmetics purchase intentions of TikTok users - Ta Huy Hung; Van Huy Trinh; Thi Mai Le (Innovative Marketing, 2025)
The rapid expansion of social media has transformed marketing strategies, with influencer marketing emerging as a powerful tool for consumer engagement. Particularly in the cosmetics business, TikTok has become well-known as a major platform where influencers influence buying habits. Given the increasing reliance on influencer recommendations, understanding the key characteristics that drive purchase intentions is crucial for businesses aiming to optimize their marketing strategies. This study investigates the impact of TikTok influencers’ characteristics, such as physical attractiveness, trustworthiness, expertise, and interactivity, on Vietnamese consumers’ cosmetics purchase intentions. Grounded in social learning theory, the research explores how users observe and emulate influencers’ behaviors in their decision-making process. A mixed-method approach was adopted, beginning with qualitative interviews with 20 TikTok users to identify key influencer attributes affecting purchase decisions. This was followed by a quantitative survey of 312 Vietnamese TikTok users with prior experience purchasing cosmetics. The study employed statistical analyses, including correlation and regression tests, to determine the significance of influencer characteristics on purchase intention. The study revealed notable gender differences in cosmetics purchasing motivations, with women showing a higher propensity to purchase due to their greater engagement with these products. The attractiveness of influencers is the strongest predictor of purchase intention, followed by trustworthiness, and interactivity, whereas expertise does not play a critical role. These insights provide valuable implications for cosmetic brands, emphasizing the importance of selecting visually appealing influencers while maintaining credibility and audience engagement.